Collaboration in times of crisis: A study on COVID-19 vaccine R&D partnerships. Issue 42 (8th October 2021) - Druedahl, Louise C.; Minssen, Timo; Price, W. Nicholson
Highlights: Vaccine partnerships tend to use next-gen vaccine platforms more than solo efforts. Collaborations focus so far more on material transfer than active knowledge sharing. Policies are needed to promote collaboration and knowledge-sharing for vaccines. Abstract: Collaboration is central for initiatives and efforts in the race to fight COVID-19, with particular focus on fostering rapid development of safe and effective COVID-19 vaccines. We investigated the types of partnerships that have emerged during the pandemic to develop these products. Using the World Health Organization's list of COVID-19 vaccine developments, we found nearly one third of all vaccine candidates were developed by partnerships, which tended to use next-gen vaccine platforms more than solo efforts. These partnerships vary substantially between materials-transfer partnerships and knowledge-sharing partnerships. The difference is important: The type of sharing between partners not only shapes the collaboration, but also bears implications for knowledge and technology development in the field and more broadly. Policies promoting fair and effective collaboration and knowledge-sharing are key for public health to avoid stumbling blocks for vaccine development, deployment, and equitable access, both for COVID-19 and expected future pandemics.